Representation of consumer culture in contemporary literature: from Roland Barthes' Mythologies to Will Self's The Sweet Smell of Psychosis - Alam, Israt (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2016.